Invarianza factorial del Launay-Slade Hallucinations Scale entre hombres y mujeres colombianos (2019)
Introduction: The Launay-Slade Hallucinations Scale (LSHS) is one of the most used tests in the hallucinations study. Its factorial structure has been described in different cultures, in the general and the clinical population. However, few studies have provided evidence of factorial equivalence regarding the sex. The aim of this investigation was to perform a measurement and structural invariance analysis of LSHS-R in an incidental sample of men and women of Colombian general population. Method: This instrumental study involving 350 inhabitants of the city of Medellín (Colombia), mostly women (64.3%), with an average age of 28.62 years. Descriptive analyzes of the items were performed before performing the analysis of invariance of measurement and structural invariance between the samples of men and women. Results: The previously reported two-dimensional model in the Colombian population, presented the best empirical adjustment indexes for men and women. Later, was obtained evidence of configurational, metric and strong invariance (measurement invariance), as well as equality of covariances and latent means (structural invariance), between men and women. On the other hand, the LSHS-R has acceptable reliability indexes. Conclusions: The two-dimensional structure of LSHS-R as well as the relationship between factors are statistically equivalent between men and women. © 2019 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.